Pre-Islamic Philosophies and Theories of Morality Across Various Religions: ما قبلِ اسلام مختلف مذاہب میں اخلاق کا فلسفہ و نظریات - Hussain, Ejaz; Naimat Khan, Dr. Mufti Shahab (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
Islam appeared in the seventh century, starting a strong basis for moral principles and ethical theories. However, this raises an important question: what moral philosophies and ethical systems existed before Islam? Were there coherent, practiced moral philosophies in pre-Islamic societies? This article explores these ancient systems, presenting an account of the pre-Islamic moral philosophies and theories that formed human thought. Through examining these earlier systems, the article addresses whether and how structured moral codes were founded before Islam’s advent. From religious traditions like those in ancient Egypt, Hinduism, Buddhism, Jainism, Zoroastrianism, and the Greek and Roman ethical schools, we observe that various cultures tried to define the principles governing good and evil, justice, duty, and the nature of virtue. Each of these systems viewed morality in different ways, often influenced by the socio-political context, religious beliefs, and philosophical inquiries of their times. For instance, Hindu and Buddhist moral theories emphasized karma, non-violence, and personal purity, while Greek philosophies like those of Socrates, Plato, and Aristotle focused on reason and virtue as the foundation of ethical conduct. The article combines these philosophies and emphasizes the importance of futher examining them one by one to understand their unique approaches and contributions. A closer analysis reveals how these moral frameworks addressed fundamental questions about human behavior, society, and justice, each leaving an imprint on the evolution of moral thought. Understanding these pre-Islamic moral theories enriches our appreciation of how Islam contributed to, expanded upon, and redefined concepts of morality for a new age.